Functional near‐infrared spectroscopy detects increased activation of the brain frontal‐parietal network in youth with type 1 diabetes. Issue 3 (15th February 2020) - Mazaika, Paul K.; Marzelli, Matthew; Tong, Gabby; Foland‐Ross, Lara C.; Buckingham, Bruce A.; Aye, Tandy; Reiss, Allan L.
Abstract: When considered as a group, children with type 1 diabetes have subtle cognitive deficits relative to neurotypical controls. However, the neural correlates of these differences remain poorly understood. Using functional near‐infrared spectroscopy (fNIRS), we investigated the brain functional activations of young adolescents (19 individuals with type 1 diabetes, 18 healthy controls, ages 8‐16 years) during a Go/No‐Go response inhibition task. Both cohorts had the same performance on the task, but the individuals with type 1 diabetes subjects had higher activations in a frontal‐parietal network including the bilateral supramarginal gyri and bilateral rostrolateral prefrontal cortices. The activations in these regions were positively correlated with fewer parent‐reported conduct problems (ie, lower Conduct Problem scores) on the Behavioral Assessment System for Children, Second Edition. Lower Conduct Problem scores are characteristic of less rule‐breaking behavior suggesting a link between this brain network and better self‐control. These findings are consistent with a large functional magnetic resonance imaging (fMRI) study of children with type 1 diabetes using completely different participants. Perhaps surprisingly, the between‐group activation results from fNIRS were statistically stronger than the results using fMRI. This pilot study is the first fNIRS investigation of executive function for individuals with type 1 diabetes. The results suggest that fNIRS is a promising functional neuroimaging resource for detecting the brain correlates of behavior in the pediatric clinic.